Penerapan SAK ETAP, Kinerja Usaha, dan Keberlanjutan UMKM di Provinsi Daerah Istimewa Yogyakarta - Ningrum Pramudiati; Anandita Zulia Putri; Anindita Imam Basri (Universitas Sarjanawiyata Tamansiswa, 2019)
This research purports to validate the influence of The Indonesian Accounting Standards for Non-Publicly-Accountable Entities (SAK ETAP) on the business performance and sustainability of micro and small business (UMKM). In addition this research purports to measure the influence of business performance on UKM’s sustainability. This research is based on primary data in the form of questionnaire using purposive sampling method and interview with selected sources. This research is expected to provide benefit for UMKM owners in their financial reports practice according SAK ETAP as to improve their business performance and sustainability. This research delineates the correlation between the implementation of SAK ETAP and the sustainability of UMKM business as mediating variable not yet found in any previous study. Keywords: the implementation of SAK ETAP, business performance, UMKM’s sustainability